Afforestation effects on SOC in former cropland: oak and spruce chronosequences resampled after 13 years. (27th May 2014) - Bárcena, Teresa G.; Gundersen, Per; Vesterdal, Lars
Abstract Chronosequences are commonly used to assess soil organic carbon (SOC) sequestration after land‐use change, but SOC dynamics predicted by this space‐for‐time substitution approach have rarely been validated by resampling. We conducted a combined chronosequence/resampling study in a former cropland area (Vestskoven) afforested with oak (Quercus robur) and Norway spruce (Picea abies) over the past 40 years. The aims of this study were (i) to compare present and previous chronosequence trends in forest floor and top mineral soil (0–25 cm) C stocks; (ii) to compare chronosequence estimates with current rates of C stock change based on resampling at the stand level; (iii) to estimate SOC changes in the subsoil (25–50 cm); and (iv) to assess the influence of two tree species on SOC dynamics. The two chronosequence trajectories for forest floor C stocks revealed consistently higher rates of C sequestration in spruce than oak. The chronosequence trajectory was validated by resampling and current rates of forest floor C sequestration decreased with stand age. Chronosequence trends in topsoil SOC in 2011 did not differ significantly from those reported in 1998, however, there was a shift from a negative rate (1998: −0.3 Mg C ha−1 yr−1) to no change in 2011. In contrast SOC stocks in the subsoil increased with stand age, however, not significantly (P = 0.1), suggesting different C dynamics in and below the former plough layer. Current rates of C change estimated by repeated sampling decreased with stand age in forest floors but increased in the topsoil. The contrasting temporal change in forest floor and mineral soil C sequestration rates indicate a shift in C source‐sink strength after approximately 40 years. We conclude that afforestation of former cropland within the temperate region may induce soil C loss during the first decades followed by a recovery phase of yet unknown duration.